Intra-Industry Trade Specialization in Türkiye’s Agricultural Sector - YÜKSEL, ŞERİF; Turgan, Erdem (Anadolu Üniversitesi, 2025)
This study examines Türkiye's agricultural trade between 2002 and 2022, focusing on the 20-year period following the 2001 economic and political crisis. Intra-industry trade theory was employed as the research method, with the Grubel-Lloyd index used for measurement. The study highlights that, under neo-liberal policies, developed economies allocate the smallest share of GDP to the agricultural sector, with industrialization and the service sector being prioritized as the foundations of wealth and development. Türkiye adopted a similar approach, shifting its focus away from agricultural growth after 1980 to prioritize investments in industry and services. However, the findings indicate that the countries deriving the most value from agricultural trade—such as the USA, the Netherlands, France, and Germany—are among the most developed. The study also reveals that Türkiye lacks a comparative advantage in the international agricultural market, having opened the sector to competition. Nonetheless, with technological advancements and branding, Türkiye could create added more value in agriculture, potentially increasing its agricultural revenues to levels closer to those of the most developed countries.
Keywords: Intra-Industry Trade; Agricultural Economics; Trade Theories